A Rapid Impedance Measurement Method Based on Superposed Modulated Square Pulse - YUE Xiaolong; ZHANG Zhenghua; SHI Hongtao; ZHANG Dong; ZHUO Fang (Kongzhi Yu Xinxi Jishu)
A new current injection method was presented for impedance measurement to solve the problems in traditional methods, such as long measuring time and inaccuracy of high frequency. It can get the grid impedance characteristics more rapidly and accurately. Sinusoidal amplitude modulation is used in this method to shift square-wave impulse signals to different frequency bands. Therefore, a signal with large frequency bandwidth and small amplitude attenuation can be obtained by superposing square pulse signals with sinusoidal amplitude modulation. When the signal is injected to the system as a current source, the simulation results demonstrate the effectiveness of this method.